2003
DOI: 10.1093/humrep/deg009
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical distribution of deeply infiltrating endometriosis: surgical implications and proposition for a classification

Abstract: Multifocality must be considered during the pre-operative work-up and surgical treatment of DIE. We propose a surgical classification based on the locations of DIE. Operative laparoscopy is efficient for bladder, USL and vaginal DIE. However, indications for laparotomy still exist, notably for bowel lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
311
3
64

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 513 publications
(390 citation statements)
references
References 27 publications
12
311
3
64
Order By: Relevance
“…If intestinal infiltration is found at transvaginal sonography, we feel that MRI or DBCE is not always needed, given that it will provide no further information when lesions are small. If there is a strong clinical suspicion of intestinal involvement, however, but transvaginal sonography shows no intestinal infiltration, MRI could be useful to exclude lesions of the upper intestinal tract [48,49,51].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If intestinal infiltration is found at transvaginal sonography, we feel that MRI or DBCE is not always needed, given that it will provide no further information when lesions are small. If there is a strong clinical suspicion of intestinal involvement, however, but transvaginal sonography shows no intestinal infiltration, MRI could be useful to exclude lesions of the upper intestinal tract [48,49,51].…”
Section: Resultsmentioning
confidence: 99%
“…Transvaginal sonographic examination is based on a detailed evaluation of organ and tissues dividing the pelvis in the anterior and posterior compartment according to the DIE classification by Chapron et al [51]. …”
Section: Ultrasound Evaluation Of Deep Infiltrating Endometriosismentioning
confidence: 99%
See 1 more Smart Citation
“…Correlacionando o estadiamento da doença 7 e a presença de endometriose em segmentos do TGI durante o procedimento da COPE, observou-se que houve correlação mais definida nos dois extremos. Jerby 12 (1999) observou lesão colorretal em 28 das 30 pacientes que pertenciam ao estádio IV. Redwine 16 (1999) afirmou que lesões nos ovários eram um sinalizador de lesões no TGI.…”
Section: Discussionunclassified
“…Although there are symptoms associated with DIE 1 , they are not specific for severity or location of DIE lesions 2 . Some studies have shown that the performance of transvaginal sonography (TVS) could be similar, if not superior, to that of magnetic resonance imaging (MRI), which is the reference technique for diagnosing endometriosis 3 -5 .…”
Section: Three-dimensional Sonorectography: a New Transvaginal Ultrasmentioning
confidence: 99%